A redox reaction-induced ratiometric fluorescence platform for the specific detection of ascorbic acid based on Ag2S quantum dots and multifunctional CoOOH nanoflakes. Issue 6 (18th January 2023) - Chen, Haoyu; Cai, Zifu; Gui, Jialing; Tang, Ying; Yin, Peng; Zhu, Xiaohua; Zhang, Youyu; Li, Haitao; Liu, Meiling; Yao, Shouzhuo
Abstract : In this work, a ratiometric fluorescent nanoplatform for the detection of ascorbic acid (AA) was constructed based on the Ag2 S quantum dots (QDs) and multifunctional hydroxyl cobalt oxide nanoflakes (CoOOH NFs). Abstract : In this work, a ratiometric fluorescent nanoplatform for the detection of ascorbic acid (AA) was constructed based on the Ag2 S quantum dots (QDs) and multifunctional hydroxyl cobalt oxide nanoflakes (CoOOH NFs). Ag2 S QDs can be assembled on the surface of CoOOH NFs by electrostatic adsorption, resulting in the quenching of the NIR fluorescence emission of Ag2 S QDs at 680 nm effectively through the inner filter effect (IFE). o -Phenylenediamine (OPD), a common substrate of oxidase-like (OXD) mimic, is rapidly oxidized into the fluorescent product of 2, 3-diaminophenazine (DAP) with the appearance of an emission peak at 575 nm under the catalysis of CoOOH NFs. After AA was added, the fluorescence emission of DAP declined because of the decline in the OXD-like activity of CoOOH NFs due to the transformation of Co 2+ . Simultaneously, Ag2 S QDs were released, accompanied by the recovery of red fluorescence. These two fluorescent signals can be excited at the same excitation wavelength, simplifying the detection procedure. Using F 575 / F 680 as the readout, the quantification of AA can be realized with the linear range and detection limit of 0.2 μM–20 mM and 0.014 μM, respectively. The ratiometric fluorescence sensor can be effectively used to determine the content of AA in real samples such as juice and serum. This work integrates the in-situ formation of the fluorescent species via the catalysis of the nanozyme and the redox reaction to destroy the CoOOH NFs nanozyme as well as the two dimensional nanoflake induced turn-off-on strategy for Ag2 S QDs, which provides a specific strategy for the selective detection of AA and may offer a reliable approach for the construction of other biosensing platforms.